1995
DOI: 10.1136/gut.36.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Profound duodenogastric reflux causes pancreatic growth in rats.

Abstract: Although duodenogastric reflux is a physiological event, excessive reflux may be a pathogenetic factor in several diseases ofthe foregut, including cancer. Long term profound duodenogastric reflux produces pancreatic and gastric tumours in rats. The trophic effect of surgically induced duodenogastric reflux on the pancreas was investigated and the mechanisms involved were examined. Rats with profound reflux from a split gastroenterostomy were compared with sham operated and unoperated controls after two and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(8 reference statements)
1
5
1
Order By: Relevance
“…Excessive DGR has been seen after gastric sur gery [24,25] and cholecystectomy [26,27], but also occurs without prior foregut surgery [4,5,28], In man, DGR has been implicated as a contributing factor in the pathogene sis of a variety of foregut diseases including gastric and duodenal ulcers [ 1 ], esophagitis [5,7] and Barrett's esoph agus [29]. Moreover, it has been suggested that DGR may induce premalignant changes in the gastric and esophage al mucosa [3,8] and DGR has been implicated as a cause of gastric stump cancer [2,3], In rats, reflux of pancraticoduodenal secretions, but not bile, causes adenocarcinoma of the stomach [2] and enhances the effect of carcinogens in the esophagus [8], It has previously been shown that the split gastrojejunostomy causes a rise in plasma CCK and gastrin and produces pancreatic growth in rats [10,11], Furthermore, long-term profound DGR in rats has been shown to produce pancreatic tumors [9], The mechanism responsible for the pancreatic growth is of interest since epidemiological studies in humans have suggested pre vious gastric surgery as a risk factor for pancreatic cancer [14][15][16], Thus DGR contributes to a variety of gastroin testinal diseases through mechanisms which have as yet not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive DGR has been seen after gastric sur gery [24,25] and cholecystectomy [26,27], but also occurs without prior foregut surgery [4,5,28], In man, DGR has been implicated as a contributing factor in the pathogene sis of a variety of foregut diseases including gastric and duodenal ulcers [ 1 ], esophagitis [5,7] and Barrett's esoph agus [29]. Moreover, it has been suggested that DGR may induce premalignant changes in the gastric and esophage al mucosa [3,8] and DGR has been implicated as a cause of gastric stump cancer [2,3], In rats, reflux of pancraticoduodenal secretions, but not bile, causes adenocarcinoma of the stomach [2] and enhances the effect of carcinogens in the esophagus [8], It has previously been shown that the split gastrojejunostomy causes a rise in plasma CCK and gastrin and produces pancreatic growth in rats [10,11], Furthermore, long-term profound DGR in rats has been shown to produce pancreatic tumors [9], The mechanism responsible for the pancreatic growth is of interest since epidemiological studies in humans have suggested pre vious gastric surgery as a risk factor for pancreatic cancer [14][15][16], Thus DGR contributes to a variety of gastroin testinal diseases through mechanisms which have as yet not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The split gastrojejunostomy was performed as previously de scribed [11], Surgery was performed after an overnight fast and the animals were deprived of water for 24 h and of food for 48 h after the procedure. The proximal jejunum was divided approximately 2 cm distal to the ligament of Treitz and the afferent loop was anasto mosed to the greater curvature of the stomach 2-3 mm distal to the squamocolumnar junction.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Rats display trophic changes in the pancreas after increased duodenogastric reflux [7]. Duodenogastric reflux is a well-known problem after BII resection in man.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the mixture of enzymes and gastric and intestinal contents could theoretically lead to a disturbed feedback regulation of pancreatic secretion. Increased duodenogastric reflux has, in rats, also been shown to cause pancreatic growth [6, 7]. It is known from animal experiments that increased levels of cholecystokinin (CCK) can induce preneoplastic and neoplastic changes in the gland, especially in the presence of carcinogens [8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that bile reflux could cause hypergastrinemia (26,30,33,34) and inhibit the release of somatostatin (35). Decreased serum levels of somatostatin increased the severity of the symptoms of hypergastrinemia, and in return, hypergastrinemia could increase bile reflux (36).…”
Section: Glandular Stomachmentioning
confidence: 99%